How Service Quality Influence Customer Satisfaction: A Case Study of Starbucks in Malaysia - Yahui, Luo; Siwen, Chen; Binti Ahmad Anis, Nur Shafinaz; Guodong, Sun; Yuanhao, Guan; Hung, Daisy Kee Mui; A., Azmi N. (International Journal of Tourism and Hospitality in Asia Pasific, 2023)
The purpose of this study is to examine how service quality in Starbucks influences customer satisfaction and loyalty towards Starbucks coffee products. Services usually related to the food and beverages industry, mainly cafes and restaurants. The quality of service provided by café services is an idea that is always used by customers in evaluating the quality of that café, and quality and taste of the food or beverages. The services provided by the company throughout the years have always called attention to the public as consumers. The respondents for this case study are the customers of Starbucks Malaysia. This report reveals the relationship between types of service quality of Starbucks and how customers get satisfied by it. From this study, it was found that the quality of service has a huge impact on customer satisfaction which most customers prefer a high-quality service. High quality service will increase customer loyalty. Besides that, high satisfaction increases customer loyalty which indicates satisfied customers definitely affect the loyalty of customers. It is suggested that the attitude of employees should be managed and trained well. For the management department, the supervision and evaluation of catering service quality and after-sales work must be strengthened.